Penananaman Nilai Karakter Siswa Kelas IV Sekolah Dasar Negeri 133 Seluma Melalui Dongeng Sayembara Pandai Tidur - Raminem Raminem (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of storytelling as a form of learning innovation fun for students, especially elementary school students 133 Seluma in learning Indonesian language. The author uses descriptive qualitative methods. The study was taken from the observation and teaching experience in the classroom. With dogeng text analysis developed as a learning material for students. The results show the theme contained in the fairy tale of Sleepy Swarm is the persistence of sleeping youth. While the mandate contained in the story that we must be good at using free time and should not distinguish between the rich and the poor. The value of the characters found in the fairy tale is honest, disciplined and socially responsible. Values ​​of characters in fairy tales or folklore from Bengkulu that often appear based on the story analyzed as much as three stories, namely the character of discipline and social care. Therefore, the character of discipline and social care is very suitable implanted for children. Keywords: Planting, Character, Fairy Tale.